Effect of different biochars on phosphorus (P) dynamics in the rhizosphere of Zea mays L. (maize) - Bornø, M.L.; Eduah, J.O.; Müller-Stöver, D.S.; Liu, F. (Plant and Soil, 2018)
AimTo investigate the effects of biochar on biological and chemical phosphorus (P) processes and identify potential interactive effects between P fertilizer and biochar on P bioavailability in the rhizosphere of maize. Methods We conducted a pot-experiment with maize in a sandy loam soil with two fertilizer levels (0 and 100 mg P kg −1) and three biochars produced from soft wood (SW), rice husk (RH) and oil seed rape (OSR). Sequential P fractionation was performed on biochar, bulk soil, and rhizosphere soil samples. Acid and alkaline phosphatase activity and root exudates of citrate, glucose, fructose, and sucrose in the rhizosphere were determined. ResultsRH and OSR increased readily available soil P, whereas SW had no effect. However, over time available P from the biochars moved to less available P pools (Al-P and Fe-P). There were no interactive effects between P fertilizer and biochar on P bioavailability. Exudates of glucose and fructose were strongly affected by especially RH, whereas sucrose was mostly affected by P fertilizer. Alkaline phosphatase activity was positively correlated with pH, and citrate was positively correlated with readily available P. Conclusion Biochar effects on biological and chemical P processes in the rhizosphere are driven by biochar properties.
Keywords: Biochar; Phosphatase activity; Phosphorus fractionation; Rhizosphere processes; Root exudates